Perceptions of music therapy for older people among healthcare professionals. Issue 1 (11th December 2015) - Khan, Waqas Ullah; Mohamad Onn Yap, Irin Arina; O'Neill, Desmond; Moss, Hilary
Abstract : Purpose of study: To investigate the perceptions of healthcare providers on music therapy and their recommendations on wider adoption in a hospital setting. Design and methods: A qualitative exploratory study employing short semistructured interviews using a thematic analysis method of data analysis. Intervention: A qualitative exploratory study, employing short semistructured interviews was conducted in March 2015 in an urban teaching hospital to explore healthcare providers' attitudes towards and recommendations on music therapy. Convenience sampling was used for recruitment of hospital staff from a multidisciplinary geriatric unit. Only staff who had exposure, awareness, or participated in the hospital music therapy programme were asked to partake in an in-depth qualitative interview. Main findings: Themes emerging reflected a belief among hospital staff that music therapy was of benefit to patients and staff; perceptions of how a hospital music therapy programme should be implemented and a desire for expansion of the music therapy programme throughout the hospital setting. Principal conclusions: Music therapy is of great importance to patients and healthcare professionals, and thus more attention is warranted to better integrate and advance this programme. This study is important because although numerous studies have examined music therapy from a patient health perspective, no report has analysed the perceptions of healthcare providers on this intervention and their recommendations on further development of music therapy services.